(3GdOQ GdfXje aj NhGU GdbQBf GdYXjes - (3eLghds
(3ChdgG (B:s
(3GdMeO ddg GdPj CWdY ef GaGb cJGHg GdYRjR fjQGJ hdYO aEf Gddg SHMGfg hJYGdi LYd cJGHg GdYRjR ddCOhGA TaGA aQGjJ Cf CLeY aj gPG GdcJGH Hjf cJGH GdHQb GddGeY hGdZjK GdgGeY hSejJgs
(3BNQgG (B:s
(3ShQI GdENdGU hef COef bQCJgG cGfJ dg ecaQI dPfhHg hfGd HgG GdeZaQI hgj fGaYI LOG aj GdOfjG hGdBNQIs
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs